Reference genes selection and validation in yam by real-time quantitative polymerase chain reaction - Linan Xing; Yanfang Zhang; Yanping Xing; Mingran Ge; Huiqin Miao; Xiuwen Huo (Scientific Reports)
Abstract Gene expression pattern analysis plays a crucial role in omics research, as it helps us understand the regulatory mechanisms of gene expression and the associated biological processes. Real-time quantitative polymerase chain reaction (q-PCR) is an efficient method for studying gene expression. Reliable q-PCR results depend on proper data normalization, which requires the use of stable reference genes. Yam, valued as both food and medicine, has significant commercial and economic potential. Its cultivation is being actively promoted in the central and western regions of Inner Mongolia. However, studies have shown that no reference gene is universally stable under all conditions. Therefore, screening and validating suitable reference genes are essential for accurately studying gene expression patterns in yam. This study evaluated nine potential reference genes based on transcriptome data of Chinese yam (Dioscorea opposita Thunb.), under various conditions, including yam tuber development, different tissues, High temperature, Low temperature, salt stress (NaCl), drought stress (PEG), abscisic acid stress (ABA), and methyl jasmonate treatment (MeJA). Using geNorm, NormFinder, BestKeeper, and RefFinder, we ranked these nine reference genes according to their expression stability. The results revealed that EIF was not suitable as a reference gene. Conversely, UBQ and PP2A were identified as the most stable and ideal reference genes for expression analysis across different conditions. Our findings provide a theoretical foundation for selecting reference genes in yam and will support more accurate gene expression studies within the genus Dioscorea.